1H-NMR Analysis of Metabolic Changes Induced by Snf1/AMP-Activated Protein Kinase During Environmental Stress Responses. Issue 3 (3rd July 2019) - Kim, Jiyoung; Oh, Junsang; Yoon, Deok-Hyo; Sung, Gi-Ho
Abstract: AMP-activated protein kinase sucrose non-fermenting 1 (Snf1) is a representative regulator of energy status that maintains cellular energy homeostasis. In addition, Snf1 is involved in the mediation of environmental stress such as salt stress. Snf1 regulates metabolic enzymes such as acetyl-CoA carboxylase, indicating a possible role for Snf1 in metabolic regulation. In this article, we performed nuclear magnetic resonance (NMR) spectroscopy to profile the metabolic changes induced by Snf1 under environmental stress. According to our NMR data, we suggest that Snf1 plays a role in regulating cellular concentrations of a variety of metabolites during environmental stress responses.